2020
DOI: 10.1364/ao.393153
|View full text |Cite
|
Sign up to set email alerts
|

Tukey’s robust M-estimator for phase demodulation of interferograms with nonuniform shifts

Abstract: In this paper, we introduce an iterative scheme for phase demodulation of interferograms with nonuniformly spaced phase shifts. Our proposal consists of two stages: first, the phase map is obtained through a least squares fitting; second, the phase steps are retrieved using a statistical robust estimator. In particular, we use Tukey’s biweighted M-estimator because it can cope with both noisy data and outliers in comparison with the ordinary least squares estimator. Furthermore, we provide the frequency descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the case of R2 Adjusted = 0.787, this indicates that the SSSYI measures 78.7% of social skills as a function of the nationality, place of residence, gender and age variables. The results showed that RMSE was = 0.712, indicating that the model fit scores below 0.712 correctly as, according to some studies, this indicates that the adjustment is adequate [141] (Table 6). In order to verify which of the variables (nationality, place of residence, gender or age) was the one that had the most weight in the research and, therefore, was the greatest predictor of social skills, a comparison of competing model coefficients was calculated.…”
Section: Data Analysis Mlr Modelmentioning
confidence: 72%
“…In the case of R2 Adjusted = 0.787, this indicates that the SSSYI measures 78.7% of social skills as a function of the nationality, place of residence, gender and age variables. The results showed that RMSE was = 0.712, indicating that the model fit scores below 0.712 correctly as, according to some studies, this indicates that the adjustment is adequate [141] (Table 6). In order to verify which of the variables (nationality, place of residence, gender or age) was the one that had the most weight in the research and, therefore, was the greatest predictor of social skills, a comparison of competing model coefficients was calculated.…”
Section: Data Analysis Mlr Modelmentioning
confidence: 72%